Successful Treatment of Long-Standing Diabetic Erectile Dysfunction Using Autologous Platelet-Rich Plasma (KYAMC Journal, 2026)
Background: Erectile dysfunction (ED) in men with long-standing type 2 diabetes mellitus is frequently refractory to standard therapies, including phosphodiesterase 5 (PDE5) inhibitors. Platelet-rich plasma (PRP) is emerging as a regenerative therapeutic modality with angiogenic, neurotrophic, and anti-fibrotic effects.Case Presentation: We report a 47 year old man with a 13 year history of diabetes and 5 year history of ED, non-responsive to maximal dose tadalafil. Standardized autologous PRP (4–5× platelet concentration) was prepared in a transfusion medicine laboratory using a double spin protocol, yielding ~4 mL PRP. Two milliliters were injected intracavernosally into each corpus cavernosum. Outcomes were measured using the International Index of Erectile Function 5 (IIEF 5), Erection Hardness Score (EHS), and penile Doppler peak systolic velocity (PSV).Results: At 12 weeks, the IIEF 5 improved from 9 to 18, EHS from Grade 1–2 to Grade 3, morning erections became regular, and intercourse related pain resolved. Penile Doppler PSV increased from 18 cm/s to 32 cm/s. No adverse events were reported.Conclusion: Autologous PRP prepared under transfusion medicine standards produced clinically meaningful erectile and hemodynamic improvement in a patient with therapy resistant diabetic ED. Further randomized trials with standardized PRP preparation are warranted.KYAMC Journal Vol. 16, No. 03, October 2025: 152-155.